PENANGANAN KRISIS REPUTASI RS PRIMA MEDIKA PEMALANG AKIBAT KELUHAN PUBLIK DI GOOGLE MAPS - Dicky Erlangga Darmawa; Yanuar Luqman (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The rapid development of digital media has transformed Google Maps into a public platform where people share their experiences with hospital services, making unresolved complaints potentially evolve into a digital reputation crisis. This study aims to analyze the emergence of a digital reputation crisis, the parties involved, and the responses of RS Prima Medika Pemalang in addressing public complaints on Google Maps. This study employed a qualitative approach with a holistic single-case study design. Data were collected through in-depth interviews with four informants, observation of Google Maps reviews, and documentation. Data were analyzed using data reduction, data display, conclusion drawing, time series analysis, and pattern matching based on Attribution Theory, Situational Crisis Communication Theory, Image Repair Theory, and Reputation Theory. The findings show that the crisis resulted from accumulated complaints regarding waiting time, administrative services, staff communication, and service quality, leading the public to attribute responsibility to the hospital. Crisis management involved regular review monitoring, complaint verification, cross-unit coordination, prompt and empathetic responses, and corrective action through service improvements. Effective crisis management depended on communication responsiveness, consistent follow-up, and coordination among the Public Relations and Marketing Unit, hospital management, and service units. Google Maps also served as an evaluation tool to improve service quality and sustain the hospital's reputation. The study concludes that effective digital reputation crisis management requires responsive communication, strong internal coordination, and organizational commitment to service improvement. It recommends strengthening digital platform monitoring, establishing standard operating procedures (SOPs) for handling digital reviews, and utilizing public reviews to support continuous service quality improvement.